2021
DOI: 10.3390/children8080615
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Pediatric Palliative Care Services in Pediatric Hematopoietic Stem Cell Transplant Centers

Abstract: Hematopoietic stem cell transplantation (HSCT) is widely used in pediatric patients as a successful curative therapy for life-threatening conditions. The treatment is intensive, with risks of serious complications and lethal outcomes. This study aimed to provide insight into current data on the place and cause of death of transplanted children, the available specialized pediatric palliative care services (SPPCS), and what services HSCT professionals feel the SPPCS team should provide. First, a retrospective da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Healthcare providers in this study recognized that a key to providing optimal pain‐related care in the HSCT unit was access to palliative care services due to their expertise in symptom management. Growing evidence supports the early integration of palliative care services for children with high‐risk cancers and undergoing HSCT therapy, yet access is offered inconsistently to families 58–60 . Children who have received palliative care services during oncology treatment have reported improvements to their quality of life and symptom burden, resulting in high acceptability with families 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare providers in this study recognized that a key to providing optimal pain‐related care in the HSCT unit was access to palliative care services due to their expertise in symptom management. Growing evidence supports the early integration of palliative care services for children with high‐risk cancers and undergoing HSCT therapy, yet access is offered inconsistently to families 58–60 . Children who have received palliative care services during oncology treatment have reported improvements to their quality of life and symptom burden, resulting in high acceptability with families 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports the early integration of palliative care services for children with high-risk cancers and undergoing HSCT therapy, yet access is offered inconsistently to families. [58][59][60] Children who have received palliative care services during oncology treatment have reported improvements to their quality of life and symptom burden, resulting in high acceptability with families. 59 Our study reported barriers to adopting the early integration of palliative care as a standard of care during HSCT therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding this predictor early in the transplant course can guide expectations for quality-of-life outcomes. Early intervention by pediatric palliative care services can help with patient and family coping and is beneficial in maximizing end-of-life planning [ 5 , 32 ]. Early intervention can also help achieve patient and family quality-of-life goals and address worries in order to aid psychological stress management throughout the transplant process [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has also been research evaluating long-term neurocognitive outcomes for pediatric patients who receive SCT [ 3 ]. This research has resulted in less toxic conditioning regimens, more uniform guidelines for patient care, and greater incorporation of supportive care measures [ 4 , 5 ]. Adult groups have created coordinated approaches to manage some pain syndromes in adult SCT recipients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Mekelenkamp et al nicely demonstrates the aforementioned difficulty of getting the pediatric palliative care team involved earlier in the disease trajectory [ 3 ]. They first looked at the place and cause of death of transplanted hematopoietic stem cell transplantation (HSCT) patients, and secondly performed a survey in which they assessed the availability of and views on specialized pediatric palliative care services (SPPCS) among 98 HSCT professionals from 54 centers in 23 countries.…”
mentioning
confidence: 99%